THE INFLUENCE OF FIBRE COMPOSITIONS AND KNITTING CONSTRUCTIONS OF PRESSURE THERAPY GLOVE FABRICS - MOHD IDRIS, MUHAMMAD KHALIS (2024)
Pressure therapy glove (PTG) is a tight-fitting glove designed to help in the management of pain and improve hand function in arthritis and treatment of hypertrophic scars. This study evaluated the effects of fibre composition, knitting construction, and heat-setting treatment on the mechanical and thermo-physiological comfort properties of PTG fabrics. Three distinct weft knitted structures were employed in this study: single jersey (S1, S2 and S3), 1x1 rib (R1), and terry fabric (T1). Each structure incorporated varying fibre compositions to explore their influence on performance. The fabrics were then categorised into different groups to measure the impact of heat setting and laundering on selected fabric properties. The results indicated that different fabric constructions exhibited different elastic properties (P<0.05), with 1x1 rib fabric demonstrating the highest load in the wale direction, and terry fabric displaying the highest load in the course direction. Fibre composition in single jersey fabrics significantly affected (P<0.05) their load requirements for extension, with 8% elastane displaying the highest resistance to stretching. Heat-setting positively affected the load capacity of the fabrics (24% - 47%). However, laundering after heat-setting decreased the load capacity (6% - 32). Water vapour permeability rate (WVTR) varied between fabrics, with single jersey fabric giving the highest WVTR value, indicating faster water vapour transmission. Heat-setting reduced fabric breathability by 8% to 25%, while laundering increased fabric breathability by 19% to 37%. Thermal resistance properties (Rct) were influenced by fabric thickness, with thicker fabrics exhibiting higher Rct values. Overall, this study provides new knowledge in the selection of fabric construction and composition as well as the effects of heat-setting and laundering on the mechanical and thermo-physiological properties of PTG fabrics. These findings could contribute to the development of PTG for improved comfort and performance.